Decolorization, Degradation, And Toxicological Analysis Of Textile Dye Effluent By Using Novel Techniques – Review (International Journal of Scientific Research and Management (IJSRM), 2015)
In textile industry during the dyeing process roughly 10% of synthetic dyes were used and let into the wastewater. Among all dyestuff Azo dyes occupies in majority, because they are extensively used in the textile, paper, food, leather, cosmetics and pharmaceutical industries. They represent chief polluting components ranging from inorganic compounds to polymers and organic elements. However prevailing effluent treatment techniques are unable to remove recalcitrant azo dyes completely from effluents because of their color fastness, solidity and highly resistance to degradation. To ensure the safety of the effluents, proper technologies need to be used for the absolute degradation of dyes. Various kinds of physico-chemical methods are used for treating textile effluent. But these methods lack in environment friendly and costeffective and hence become commercially unattractive. On other hand nature boon with many microorganisms belonging to the different taxonomic groups of bacteria, fungi, actinomycetes and algae have been reported for their ability to decolourize azo dyes. Thus biodegradation technique approach will be of eco friendly with no secondary hazard. Nowadays, in advance, enzymes can be utilized to develop remediation processes that are ecofriendly than conventional techniques. Their versatility and efficiency even in mild reaction conditions gives them an advantage over other methods. The biological origin of enzymes reduces their adverse impact on the environment, thereby making enzymatic wastewater treatment an ecologically sustainable technique. We focused on the enzymatic mechanisms involved in the bacterial degradation of azo dyes, and also investigated the toxicity level. Thus overview of this review deals with the bacterial decolorization/degradation of azo dyes and enumerate the role of these processes for the treatment of textile dye effluent. In the present review the decolorization and degradation of azo dyes by fungi, yeast and bacteria have been cited along with the toxicological, cytotoxicity, genotoxicity studies were discussed and also the role of enzymes involved in the microbial decolorization of azo dyes have been discussed.